Share your voice (Papeles, 2019)
Taking into account the importance of reading in the teaching-learning process, this research aimed to identify methodological aspects of reading aloud that contribute to the formation of autonomous readers of the 602 J.M. of the Misael Pastrana Borrero District Educational Institution in Bogotá. This research offers the opportunity to show the scope, successes, difficulties and evaluation of the process of implementing a didactic sequence of reading aloud and its impact on the formation of autonomous readers. The results of the field work and the findings of the research exercise are widely described. The document ends with the presentation of the conclusions and recommendations that suggest a set of strategies for the promotion ofreading aloud.
Keywords: reading aloud; autonomous readers